Kino‐Geometric Modeling: Insights into Protein Molecular Mechanisms - Budday, Dominik; Leyendecker, Sigrid; van den Bedem, Henry (Proc. Appl. Math. Mech (PAMM), 2019)
Proteins are dynamic macromolecules that perform an immense variety of biological functions on a broad range of spatio‐temporal scales. Their conformational ensemble is a fundamental determinant of functionality in health and disease. While computational advances have increasingly enabled the computation of atomically detailed trajectories from Molecular Dynamics (MD) simulations, there remain considerable drawbacks when aiming for fast, yet elaborate insights into the molecular mechanisms of function. Here, we explore the potential of kinematics and geometry based methods, inspired from traditional robotics, to study protein conformational dynamics. Using geometric tools, we demonstrate insights into molecular mobility from instantaneous rigidity and flexibility analysis on selected example systems. Resulting motions from kinematically sampling along collective degrees of freedom show qualitative and quantitative agreement with motions from MD simulations. Coupled to sophisticated motion planning strategies, our approach is capable of providing structural ensemble representations from sparse experimental data such as double electron‐electron resonance (DEER) that remain difficult to interpret otherwise. Overall, we establish our Kino‐Geometric Sampling tool KGS as an efficient alternative to obtain high‐level insights into molecular mechanisms across scales, with ample applications in protein design and human health.<br